Purchase decision-making is modulated by vestibular stimulation - Preuss, Nora; Mast, Fred; Hasler, Gregor (Frontiers in Behavioral Neuroscience, 2014)
Purchases are driven by consumers’ product preferences and price considerations. Using caloric vestibular stimulation (CVS), we investigated the role of vestibular-affective circuits in purchase decision-making. CVS is an effective non-invasive brain stimulation method, which activates vestibular and overlapping emotional circuits (e.g. the insular cortex and the anterior cingulate cortex). Subjects were exposed to CVS and sham stimulation while they performed two purchase decision-making tasks. In Experiment 1 subjects had to decide whether to purchase or not. CVS significantly reduced probability of buying a product. In Experiment 2 subjects had to rate desirability of the products and willingness to pay while they were exposed to CVS and sham stimulation. CVS modulated desirability of the products but not willingness to pay. The results suggest that CVS interfered with emotional circuits and thus attenuated the pleasant and rewarding effect of acquisition, which in turn reduced purchase probability. The present findings contribute to the rapidly growing literature on the neural basis of purchase decision-making.